Filsafat Pendidikan Islam dalam Perspektif Pendidikan Multikultural - Aprilita Hajar; Noor Hamid; Abdul Haris; Rosichin Mansur (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
This article discusses the Islamic education perspective in the context of multicultural education and the urgency of integrating multiculturalism into education. The researcher employs qualitative research methods and references literary sources as data references. Multicultural-oriented Islamic education instils awareness of the importance of living with values of cooperation, tolerance, and harmony amid differences. Consequently, this approach offers the best path to address religious conflicts. The focus is on the educational realm because it possesses characteristics of open-minded thinking, learning to live with differences and mutual understanding. Multicultural-oriented Islamic education serves as a solution to existing or potential conflicts. Thinking deeply, as defined by the philosophy of Islamic education, aids in examining various issues related to Islamic education. The results of this research include the emergence of an understanding of the essence of Islamic education and how the principles, objectives, and functions of multicultural education are perceived from the perspective of Islamic educational philosophy.